2017
DOI: 10.1039/c6cp08168a
|View full text |Cite
|
Sign up to set email alerts
|

Detection of electron tunneling across plasmonic nanoparticle–film junctions using nitrile vibrations

Abstract: The significant electric field enhancements that occur in plasmonic nanogap junctions are instrumental in boosting the performance of spectroscopy, optoelectronics and catalysis. Electron tunneling, associated with quantum effects in small junctions, is reported to limit the electric field enhancement. However, observing and quantitatively determining how tunneling alters the electric fields within small gaps is challenging due to the nanoscale dimensions and heterogeneity present experimentally. Here we repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
54
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(64 citation statements)
references
References 83 publications
9
54
1
Order By: Relevance
“…Similarly, the 1588 cm –1 assigned to molecule–surface binding, shifts 7 cm –1 after eight successive intervals of pumping time. Previous studies have demonstrated that molecules are capable of directly measuring the modulation of local electromagnetic fields due to electron tunneling in plasmonic nanogaps. , The resulting time-dependent vibrational shifts are due to a buildup of charge due to optical rectification in strongly coupled nanoparticle systems. A recent study on charge buildup of Au nanoparticles concluded that steady-state light excitation can lead to photoelectrochemical potentials as high as 240 mV .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the 1588 cm –1 assigned to molecule–surface binding, shifts 7 cm –1 after eight successive intervals of pumping time. Previous studies have demonstrated that molecules are capable of directly measuring the modulation of local electromagnetic fields due to electron tunneling in plasmonic nanogaps. , The resulting time-dependent vibrational shifts are due to a buildup of charge due to optical rectification in strongly coupled nanoparticle systems. A recent study on charge buildup of Au nanoparticles concluded that steady-state light excitation can lead to photoelectrochemical potentials as high as 240 mV .…”
Section: Discussionmentioning
confidence: 99%
“…30 mV across the nanogap. Schultz and co-workers found optical rectification by aggregates of Au nanorods with nanogaps. Under visible-light excitation, the nanostructures were found to sustain a DC potential, as evidenced by the Stark shift of the vibrational mode of a reporter molecule.…”
Section: Light-induced Potentials In Plasmonic Nanostructuresmentioning
confidence: 99%
“…56 In a chemically inert environment, the hot carriers transfer their energy to the metal lattice, converting the absorbed light into heat. 5, 78 These plasmonic properties of gold NPs have been used for various applications, such as: SERS, 913 TERS, 1415 solar energy conversion, 1618 photocatalysis, 1920 and photothermal therapy. 2123 …”
Section: Introductionmentioning
confidence: 99%